Marketing and postmodernity: New challenges in a new context - Arbaiza Rodríguez, Francisco (2022)
In the last decades of last century -and early years of the current- we have gone through radical changes in core areas of human activity as social, cultural, economic and political. New trends have spread around the world, especially in western societies and those with established western influence. Many scholars from different disciplines attribute these changes in life and in the social conditions as a result of the same phenomenon known as postmodernism. Under this premise, this paper attempts to explain how this condition is affecting the current marketing theory and determined the conditions under which it operates its practice. Its influence becomes more important when considering the leading role played by the marketing in the postmodern phenomenon.